Making War Pay for War. Napoleon and the Dutch War Subsidy, 1795-1806. - Hay, Mark Edward (TSEG - The Low Countries Journal of Social and Economic History, 2020)
Just over one decade ago, Pierre Branda published a study of Napoleonic public finance. The study marks a turning point in the historiography of Napoleonic war financing because, through relying on well-researched quantitative data, Branda lays to rest the long-held myth that Napoleon ‘made war pay for war’. However, the Franco-centric conceptualisation of Napoleonic resource extraction and the temporal delineation have resulted in a prism that omits certain sources of revenue. This omission has a bearing on Branda’s overall assessment of Napoleonic war financing. Through exploring French resource extraction in the Netherlands through forcing the Dutch to pay for the maintenance of a French contingent, this article builds on Branda’s work to shed a new light on the success of Napoleonic resource extraction and war financing.